The IoT-Distributed Energy Efficient Clustering (IoT-DEEC) Routing Protocol for Wireless Sensor Networks - Ibrahem, Reham Ismail; Hamza, Ekhlas Kadhum (Engineering, Technology & Applied Science Research, 2025)
Wireless Sensor Networks (WSNs) consist of many small devices that have a scarce amount of energy, and an efficient routing protocol is needed to prolong its lifetime. Although most cluster-based related protocols deal with energy heterogeneity, they tend to disregard two important values, the distance between the nodes and the Base Station (BS) and the average inter-node distance. The present paper proposes IoT-DEEC, a hierarchical, multi-radio, multi-channel protocol that tries to overcome these limitations. The selection of Cluster Head (CH) is done on the basis of residual energy, node-to-CH distance, and CH-to-BS distance while a sleep and wake-up mechanism is involved to save energy. Distant node management is a IoT-DEEC feature that implements a threshold energy model. The simulation results indicate that IoT-DEEC drastically enhances the performance of the network compared to TDEEC, with more alive nodes per round, less dead nodes, more packet transmissions to the BS, and less energy consumption.